Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Discover comprehensive solutions to your questions from a wide network of experts on our user-friendly platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Certainly! Let's break down the given expression step-by-step:
The expression we need to evaluate is:
[tex]$\left[8^{-\frac{2}{3}} \times 2^{\frac{1}{2}} \times 25^{-\frac{5}{4}}\right] \div\left[32^{-\frac{2}{5}} \times 125^{-\frac{5}{6}}\right].$[/tex]
### Step-by-Step Solution:
#### 1. Simplify the numerator.
The numerator can be expressed as:
[tex]$8^{-\frac{2}{3}} \times 2^{\frac{1}{2}} \times 25^{-\frac{5}{4}}.$[/tex]
Let's simplify each term separately.
- [tex]\( 8 = 2^3 \)[/tex], so:
[tex]\[ 8^{-\frac{2}{3}} = (2^3)^{-\frac{2}{3}} = 2^{3 \times -\frac{2}{3}} = 2^{-2} = \frac{1}{4}. \][/tex]
- [tex]\( 2^{\frac{1}{2}} \)[/tex] remains as it is, which is [tex]\( \sqrt{2} \)[/tex].
- [tex]\( 25 = 5^2 \)[/tex], so:
[tex]\[ 25^{-\frac{5}{4}} = (5^2)^{-\frac{5}{4}} = 5^{2 \times -\frac{5}{4}} = 5^{-\frac{5}{2}}. \][/tex]
Thus, the simplified numerator is:
[tex]\[ \frac{1}{4} \times \sqrt{2} \times 5^{-\frac{5}{2}}. \][/tex]
#### 2. Simplify the denominator.
The denominator can be expressed as:
[tex]$32^{-\frac{2}{5}} \times 125^{-\frac{5}{6}}.$[/tex]
Let's simplify each term separately.
- [tex]\( 32 = 2^5 \)[/tex], so:
[tex]\[ 32^{-\frac{2}{5}} = (2^5)^{-\frac{2}{5}} = 2^{5 \times -\frac{2}{5}} = 2^{-2} = \frac{1}{4}. \][/tex]
- [tex]\( 125 = 5^3 \)[/tex], so:
[tex]\[ 125^{-\frac{5}{6}} = (5^3)^{-\frac{5}{6}} = 5^{3 \times -\frac{5}{6}} = 5^{-\frac{5}{2}}. \][/tex]
Thus, the simplified denominator is:
[tex]\[ \frac{1}{4} \times 5^{-\frac{5}{2}}. \][/tex]
#### 3. Combine the simplified terms.
Now, rewrite the original expression using the simplified numerator and denominator:
[tex]\[ \frac{\frac{1}{4} \times \sqrt{2} \times 5^{-\frac{5}{2}}}{\frac{1}{4} \times 5^{-\frac{5}{2}}}. \][/tex]
#### 4. Simplify the fraction.
Notice that both the numerator and the denominator have the common factors [tex]\(\frac{1}{4}\)[/tex] and [tex]\(5^{-\frac{5}{2}}\)[/tex]. So, these common factors will cancel out:
[tex]\[ \frac{\left(\frac{1}{4} \times \sqrt{2} \times 5^{-\frac{5}{2}}\right)}{\left(\frac{1}{4} \times 5^{-\frac{5}{2}}\right)} = \sqrt{2}. \][/tex]
Therefore, the simplified value of the given expression is:
[tex]\[ \sqrt{2}. \][/tex]
So, the final result is [tex]\(\boxed{\sqrt{2}}\)[/tex].
The expression we need to evaluate is:
[tex]$\left[8^{-\frac{2}{3}} \times 2^{\frac{1}{2}} \times 25^{-\frac{5}{4}}\right] \div\left[32^{-\frac{2}{5}} \times 125^{-\frac{5}{6}}\right].$[/tex]
### Step-by-Step Solution:
#### 1. Simplify the numerator.
The numerator can be expressed as:
[tex]$8^{-\frac{2}{3}} \times 2^{\frac{1}{2}} \times 25^{-\frac{5}{4}}.$[/tex]
Let's simplify each term separately.
- [tex]\( 8 = 2^3 \)[/tex], so:
[tex]\[ 8^{-\frac{2}{3}} = (2^3)^{-\frac{2}{3}} = 2^{3 \times -\frac{2}{3}} = 2^{-2} = \frac{1}{4}. \][/tex]
- [tex]\( 2^{\frac{1}{2}} \)[/tex] remains as it is, which is [tex]\( \sqrt{2} \)[/tex].
- [tex]\( 25 = 5^2 \)[/tex], so:
[tex]\[ 25^{-\frac{5}{4}} = (5^2)^{-\frac{5}{4}} = 5^{2 \times -\frac{5}{4}} = 5^{-\frac{5}{2}}. \][/tex]
Thus, the simplified numerator is:
[tex]\[ \frac{1}{4} \times \sqrt{2} \times 5^{-\frac{5}{2}}. \][/tex]
#### 2. Simplify the denominator.
The denominator can be expressed as:
[tex]$32^{-\frac{2}{5}} \times 125^{-\frac{5}{6}}.$[/tex]
Let's simplify each term separately.
- [tex]\( 32 = 2^5 \)[/tex], so:
[tex]\[ 32^{-\frac{2}{5}} = (2^5)^{-\frac{2}{5}} = 2^{5 \times -\frac{2}{5}} = 2^{-2} = \frac{1}{4}. \][/tex]
- [tex]\( 125 = 5^3 \)[/tex], so:
[tex]\[ 125^{-\frac{5}{6}} = (5^3)^{-\frac{5}{6}} = 5^{3 \times -\frac{5}{6}} = 5^{-\frac{5}{2}}. \][/tex]
Thus, the simplified denominator is:
[tex]\[ \frac{1}{4} \times 5^{-\frac{5}{2}}. \][/tex]
#### 3. Combine the simplified terms.
Now, rewrite the original expression using the simplified numerator and denominator:
[tex]\[ \frac{\frac{1}{4} \times \sqrt{2} \times 5^{-\frac{5}{2}}}{\frac{1}{4} \times 5^{-\frac{5}{2}}}. \][/tex]
#### 4. Simplify the fraction.
Notice that both the numerator and the denominator have the common factors [tex]\(\frac{1}{4}\)[/tex] and [tex]\(5^{-\frac{5}{2}}\)[/tex]. So, these common factors will cancel out:
[tex]\[ \frac{\left(\frac{1}{4} \times \sqrt{2} \times 5^{-\frac{5}{2}}\right)}{\left(\frac{1}{4} \times 5^{-\frac{5}{2}}\right)} = \sqrt{2}. \][/tex]
Therefore, the simplified value of the given expression is:
[tex]\[ \sqrt{2}. \][/tex]
So, the final result is [tex]\(\boxed{\sqrt{2}}\)[/tex].
Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.